1980
DOI: 10.1136/bmj.281.6249.1179
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric morbidity and physical toxicity associated with adjuvant chemotherapy after mastectomy.

Abstract: Blood oxygen and carbon dioxide pressures during three admissions. Results are given under days after admission in each month Month of admission Pressure (kPa) March

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(24 citation statements)
references
References 2 publications
0
24
0
Order By: Relevance
“…This is of value since early detection and treatment of psychiatric illness has been found to improve outcome (Maguire et al, 1980), as has targeted intervention for patients at high risk (Moorey et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is of value since early detection and treatment of psychiatric illness has been found to improve outcome (Maguire et al, 1980), as has targeted intervention for patients at high risk (Moorey et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The psychiatric morbidity among cancer patients has been estimated previously and it has been found that approximately 25-30% of all cancer patients develop clinically significant anxiety or depression within 2 years of diagnosis (Maguire, 1992;Greer, 1994). Several risk factors for development of psychiatric disorder have been identified and examined.…”
mentioning
confidence: 99%
“…Numerous instruments have been described to quantify physical or psychological problems in patients. Most are lengthy and require specially trained personnel to use them but they may be valuable in oncological research for detailed study of particular aspects of patients' lives (Maguire et al, 1980;McArdle et al, 1981). Fewer attempts have been made to produce instruments specifically for use in oncological research or practice (Priestman & Baum, 1976;Eisenberg & Goldenburg, 1966;Izsak & Medelie, 1971;Worden & Weisman, 1977;Padilla et al, 1981;Craig et al, 1974), and most of these have not been formally evaluated or widely used.…”
Section: Correlations Between Scores For Items Within Thementioning
confidence: 99%
“…
Summary Two hundred and twenty-two women with advanced cancer of the breast were asked to complete two previously validated self-assessment questionnaires (Hospital Anxiety and Depression Scale (HADS) There has been extensive investigation into the psychological sequelae of early breast cancer and its treatment (Maguire et al, 1978;Maguire et al, 1980;Morris et al, 1977;Robert et al, 1972) but there are few data concerning the prevalence of depression and anxiety in patients with advanced disease. There is a need to determine the extent and severity of affective disorder in patients receiving palliative treatment for breast cancer and to find out whether such disorder is transient or warrants intervention.
…”
mentioning
confidence: 99%